2013
DOI: 10.1177/2150129713476951
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Older Adults

Abstract: Asthma is a serious health issue for older adults. Among Australians aged 55 years and older, asthma prevalence, morbidity, and mortality are relatively high by international comparison and compared to other age groups. As people age, the diagnosis of asthma becomes more complicated, primarily due to comorbid conditions. Treatment and self-management are also more difficult in this age group due to the different medications prescribed for multiple conditions. At the same time, older adults do not perceive that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This has been revealed in other studies that reported bill boards as effective tools for mass awareness [23, 24]. Other studies have suggested that messages on the bill board must be displayed with pictures that can easily be comprehended by the general public [23, 25].…”
Section: Discussionmentioning
confidence: 66%
“…This has been revealed in other studies that reported bill boards as effective tools for mass awareness [23, 24]. Other studies have suggested that messages on the bill board must be displayed with pictures that can easily be comprehended by the general public [23, 25].…”
Section: Discussionmentioning
confidence: 66%
“…Recent reviews have recommended that governments and communities undertake public health programs to raise community awareness of asthma amongst older adults, enhance older adults’ understanding of asthma, and address commonly held misperceptions [5,25]. While there are several evidence-based frameworks available to structure health promotion interventions, the social marketing framework has been particularly effective in health promotion to increase knowledge of particular health issues and change targeted health behaviours [26-28].…”
Section: Introductionmentioning
confidence: 99%